Towards a Non-Reactionary Humanistic Approach to AI - Jurado-González, Javier (Razón y fe, 2024)
Numerous publications are engaged in deflating the inflated expectations surrounding recent advancement in AI. However, within certain humanist circles where conservative skepticism regarding novelties is prevalent, it is convenient to reflect on the converse extreme: the complacency of viewpoints that rely on weak arguments and outdated concepts which have been surpassed in both scientific and philosophical literature. These perspectives tend to adopt a reactionary stance towards AI, defensively holding onto any assertion that preserves human uniqueness, even at the expense of intellectual integrity. Such a defensive posture steadfastly asserts that AI will never attain human singularity. Nevertheless, it is conceivable to embrace humanistic perspectives that remain receptive to AI’s advancements, addressing its current challenges while engaging in dialogue and refining arguments. This can be achieved through several approaches, including dignifying human misery, fostering interdisciplinary collaboration, and exercising prudence, courtesy, and the suspension of judgment when warranted.
Keywords: philosophy of artificial intelligence; philosophy of mind; technological humanism; semantic grounding; hard problem of consciousness